2020
DOI: 10.1016/j.kint.2020.01.033
|View full text |Cite
|
Sign up to set email alerts
|

A deletion in the N-terminal polymerizing domain of laminin β2 is a new mouse model of chronic nephrotic syndrome

Abstract: The importance of the glomerular basement membrane (GBM) in glomerular filtration is underscored by the manifestations of Alport and Pierson syndromes, caused by defects in type IV collagen a3a4a5 and the laminin b2 chain, respectively. Lamb2 null mice, which model the most severe form of Pierson syndrome, exhibit proteinuria prior to podocyte foot process effacement and are therefore useful for studying GBM permselectivity. We hypothesize that some LAMB2 missense mutations that cause mild forms of Pierson syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…The relative importance of polymerisation to LAMA5 function during fetal development is poorly understood. However, mutations in LAMB2 LN domains cause Pierson syndrome, indicating that abrogated polymerisation is important for maintaining the in vivo integrity and functionality of the glomerular BM (McKee et al, 2018;Funk et al, 2018Funk et al, , 2020. Moreover, recent crystallographic studies have identified a protein interface within the LN domain in the region of a PLENGE sequence motif which appears to be important for this oligomerisation (Hussain et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The relative importance of polymerisation to LAMA5 function during fetal development is poorly understood. However, mutations in LAMB2 LN domains cause Pierson syndrome, indicating that abrogated polymerisation is important for maintaining the in vivo integrity and functionality of the glomerular BM (McKee et al, 2018;Funk et al, 2018Funk et al, , 2020. Moreover, recent crystallographic studies have identified a protein interface within the LN domain in the region of a PLENGE sequence motif which appears to be important for this oligomerisation (Hussain et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…E884G is capable of interacting with other laminin chains to some degree, as was observed in the LAMB2-Del44 mice [16], allowing trimer formation. Conversely, we observed that that…”
Section: Firstly Lama5mentioning
confidence: 73%
“…Mutations in the LAMB2 gene, encoding the laminin β2 chain, cause disorders with a wide clinical spectrum. Truncating mutations lead to Pierson syndrome, characterised by microcoria, congenital NS, muscular hypotonia and neurodevelopmental defects [12][13][14], whilst missense variants cause a much milder variant of Pierson syndrome or isolated congenital NS [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…[ 41 ] Loss or mutation to structural components of the GBM leads to proteinuria and renal disease. [ 42–44 ] GBM/podocyte interactions are also critical to maintaining a stringent size‐selective glomerular filtration barrier, and loss of proteins that mediate podocyte–GBM adhesion leads to proteinuria in animal models. [ 22,23,45 ] This suggests that both the GBM and the podocyte/GBM interface are critical for proper function of the glomerular filtration barrier.…”
Section: Discussionmentioning
confidence: 99%